A arte equilibrista de envelhecer em meio às desigualdades sociais : reflexões a partir dos participantes de um grupo de convivência para idosos em tempos de pandemia de COVID-19 - Shirly Ferreira de Souza (2023)
Since the middle of the 20th century, the phenomenon of population aging has been observed throughout the world. In developing countries, such as Brazil, this phenomenon occurs amid historic social inequalities, resulting in markedly poor old age. The chosen approach was to relate social inequalities and aging, based on a discussion of social capital, exemplified not only, but mainly by social groups for the elderly, carried out by the Coexistence and Strengthening of Bonds Service/Assistance Reference Center Social – SCFV/CRAS, the majority of which are low-income people. Qualitative methodology was used, employing the semi-structured interview technique, as well as content analysis, to interpret the interviews. Among the results found, we highlight that elderly people are more providers than recipients of resources throughout their lives, only needing support when they are much older; ; as well as the family demonstrated to be the main source of support for this age group, with the intergenerational exchange of support being based on the logic of reciprocity.